2015
DOI: 10.1039/c5cc00902b
|View full text |Cite
|
Sign up to set email alerts
|

A new fluorogenic probe for the selective detection of carbon monoxide in aqueous medium based on Pd(0) mediated reaction

Abstract: A coumarin-based fluorogenic probe, PCO-1, senses carbon monoxide (CO) selectively in HEPES buffer at pH 8.0 through the intramolecular cyclization-elimination pathway based on Pd(0) mediated reaction. The probe exhibits a 'turn-on' response of CO over a variety of relevant reactive oxygen, nitrogen and sulfur species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 30 publications
1
90
0
Order By: Relevance
“…The major obstacle in this area is the lack of real-time approaches to selectively track CO in biological systems. Some established approaches for CO detection include gas chromatography, chromogenic detection, laser sensor-infrared absorption, electrochemical assays, etc, [5][6][7][8] [15][16][17][18][19][20] including our newly reported probe. 21 However, almost all of these probes display emissions in the visible region, which greatly restricts their applications in biological imaging, due to the strong autofluorescence and limited tissue penetration.…”
Section: Introductionmentioning
confidence: 99%
“…The major obstacle in this area is the lack of real-time approaches to selectively track CO in biological systems. Some established approaches for CO detection include gas chromatography, chromogenic detection, laser sensor-infrared absorption, electrochemical assays, etc, [5][6][7][8] [15][16][17][18][19][20] including our newly reported probe. 21 However, almost all of these probes display emissions in the visible region, which greatly restricts their applications in biological imaging, due to the strong autofluorescence and limited tissue penetration.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the detection limit, following equation was used. DL= 3σ/S, where σ is the standard deviation of seven replicate measurements of the zero level (σ zero ) and S is the slope of the curve . The fluorescent titration profile of LH with ClO − ion demonstrated that the detection limit of ClO − ion is 75.9 nM (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…In 2015, Dhara et al reported a coumarin-based uorescent probe 38 for the detection of CO through a Pd(0)-mediated intramolecular cyclization-elimination reaction. 56 The weak uorescence intensity of the probe was obtained by protecting the hydroxyl group of coumarin via allyl-functionalized carbamate. The proposed detection mechanism may involve the following processes.…”
Section: Tsuji-trost Reactionmentioning
confidence: 99%